Vocational School Students' Attitudes Towards Internet - Tuncer, Murat; Dogan, Yunus; Tanas, Ramazan (Elsevier Science Bv, 2013)
Internet is shown among the main ways of learning in many recent research findings. Many masses like personnel and students prefer meeting their need for obtaining knowledge with internet above all. This positive impact of internet on learning can be better increased with the determination and direction of various psychological perceptions of the learners'. One of these psychological traits is attitude towards Internet. In this study, 265 undergraduate students', from various departments of Tunceli Vocational School of Tunceli University, attitudes towards internet were investigated. The Attitude Towards Internet Scale was used as the data collection instrument. The opinions gathered with the application of the scale were compared in terms of gender, grade, experience of computer education, age and field of study variables. Some of the findings are as following: the attitude towards internet does not differentiate meaningfully in terms of gender and grade variables; whereas there is a meaningful difference of opinions in terms of the field of study variable. (C) 2013 The Authors. Published by Elsevier Ltd.
13th International Educational Technology Conference -- OCT 30-NOV 01, 2014 -- Lisbon, PORTUGAL
Keywords: Attitude Towards Internet; Internet; Learning; Vocational School Students